Knowledge and Awareness of Radiation Protection Among Healthcare Workers: A Cross-Sectional Study - Berliana Devianti Putri; Anisa Dewi Setiawati; Winda Kusumawardani; Cendra Devayana Putra; Gabriel Loi (Health Frontiers: Multidisciplinary Journal for Health Professionals, 2026)
Ionising radiation from diagnostic procedures poses significant occupational risks to healthcare workers (HCWs), yet awareness remains suboptimal in many settings, particularly in low- and middle-income countries. This cross-sectional study assessed radiation protection knowledge and awareness among 140 HCWs from inpatient, intensive care, and emergency units in Indonesia, identifying independent predictors of awareness. Knowledge was evaluated using a validated 15-item instrument (categorized as poor, acceptable, or good), while awareness was measured as a binary outcome. Data were analyzed using Pearson’s chi-square test and multivariable binary logistic regression, adhering to STROBE guidelines. The sample was predominantly female (69.3%) with bachelor’s degrees (57.1%). Overall, 46.4% demonstrated good knowledge, 48.6% acceptable, and 5.0% poor, while 68.6% were classified as aware. Multivariable analysis revealed that knowledge level was the sole independent predictor of awareness: compared to poor knowledge, acceptable knowledge significantly increased awareness odds (aOR = 3.48; 95% CI: 1.12–10.80; p = 0.031), as did good knowledge (aOR = 8.65; 95% CI: 2.10–35.60; p = 0.003). These findings confirm that radiation protection knowledge strongly and independently drives awareness among clinical staff. Consequently, healthcare institutions must prioritize continuous, evidence-based radiation safety education—particularly for personnel in high-exposure units—as the foundational strategy to effectively bridge the knowledge–awareness gap and mitigate occupational radiation risks.